Learning from the history of alternative communication networks. Issue 1 (1st April 2020) - Tréguer, Félix; Trudel, Dominique; Dulong de Rosnay, Mélanie
This article explores the legal, economic and governance challenges to the sustainability of contemporary alternative Community Networks by drawing lessons and parallels from eight historical precedents. Building on academic literature related to alternative and community media, the article lays out an encompassing definition of alternative networks (or 'alternets') and develops a multidisciplinary approach to comparative history. After briefly presenting eight case studies (three independent telephone networks of the late nineteenth century; three Free Radios of the 1950s, 1960s and 1970s; two Community Networks providing Internet access in the 1990s), the article then draws from these case studies to identify key recurring challenges that can inform present-day initiatives, namely, the articulation of local community with global connectivity, the development of political advocacy capacities aimed at influencing the law and technology, the creation of appropriate resources aimed at resisting co-optation, and the need to build collective cohesion and mechanisms to handle disagreements.